Avaliação do uso e cobertura do solo e fragmentação florestal utilizando dados do Projeto Terraclass no município de Primavera-PA em 2004 e 2014 - ROCHA, Nívia Cristina Vieira (2019)
Changes related to land use and land cover take on large proportions over the years, requiring an environmental assessment for the application of measures that are effective in the conservation of forest areas. The research is carried out in the municipality of Primavera, located in the northeast of the state of Pará, with an extension of 254 km2 approximately. The objective of this study is to analyze the land use and cover for the municipality of Primavera and the changes in the landscape between the years 2004 and 2014, through local forest fragmentation. For this, data from the TerraClass project were used, which enabled the elaboration of land use and cover maps for the study period. In addition to these data, two classes were selected for the analysis of forest fragmentation of the municipality, forest classes and secondary vegetation. For this process, landscape ecology metrics were used, which provide spatial indicators related to the ecological conditions of forest fragments. From the use of this method, it was observed some characteristics that occurred in the municipality during the interval of ten years, for example, the increase of urban areas and the increased vulnerability of the fragments to the forest class and fragmentation to the secondary vegetation class.